Association between personal characteristics and musculoskeletal disorders among the dental surgeons working in Dhaka city (Update Dental College Journal, 2021)
Background: Occupational hazards are common in different working populations. Musculoskeletal disorders (MSDs) are the most important occupational hazards particularly in dental professionals. This disorder which is multi factorial in origin has relation with different characteristics. The study aims to find out the association between personal characteristics in terms of socio demographic, occupation characteristics and MSDs among the dental surgeons working in Dhaka city.Methods: Present cross sectional study was conducted among purposively selected 290 dental surgeons working in thirteen private and public tertiary level hospitals in Dhaka city. A structured questionnaire was used for data collection including socio demographic and occupational characteristics which reflect the personal characteristics of dental surgeons. To determine the MSDs, Nordic Musculoskeletal Questionnaire (NMQ) was used which records the prevalence of MSDs in terms of musculoskeletal symptoms. Collected data were analyzed by using SPSS software (Version 22).Results : Almost 64.0% dental surgeons experienced MSDs in past 12 months in at least one region of the body, and the major affected part was neck, followed by lower back, shoulders and hands / wrists. Regarding the relationship between personal characteristics and MSDs, present study found significant relationship exists between some socio demographic characteristics like age, physical activity; some occupational characteristics like work status, practicing area, practicing four handed dentistry, maintaining back position upright, psychosocial stress with MSDs in chi square test.Conclusion: This study concludes that the existence of significant relationship between different personal characteristics and MSDs among dental surgeons which need to be address properly, so that dental professionals will be able to take corrective measures to combat with this disorder.Update Dent. Coll. j: 2021; 11 (1): 11-15